Cegah Scabies Melalui Penyuluhan (PHBS) Dalam Rangka Mewujudkan Sanitasi sehat,bersih Dan Bebas Stunting - Salwa, Ahtiyah; Emsiana, Mela; Amsah , Muhammad; Retni, Retni; Sudiyanto, Sudiyanto (Utami Publisher, 2025)
Scabies is a contagious skin disease caused by infestation of the Sarcoptes scabiei mite. This condition commonly occurs in densely populated environments with poor personal hygiene, such as Islamic boarding schools (pesantren), dormitories, or correctional facilities. The main symptom of scabies is intense itching, especially at night, accompanied by skin lesions such as rashes and small bumps. Transmission occurs through direct person-to-person contact or through contaminated personal items. Prevention includes maintaining personal hygiene, avoiding the sharing of personal belongings, and providing proper treatment to infected individuals and close contacts. Health education for students and caregivers in pesantren is crucial to increase awareness, prevent transmission, and create a clean and healthy environment. Early treatment and continuous education are key to controlling scabies in densely populated settings.